Allgemeinbildung and digital technologies in mathematics education: a review - Johansen, Stine Gerster (NOMAD Nordic Studies in Mathematics Education, 2023)
The conception of Allgemeinbildung in Danish schools might be influenced by the inclusion of digital technologies in mathematics education. This paper presents the results of a literature review aimed at answering the potential and challenges posed by the inclusion of digital technologies in mathematics education in relation to students’ Allgemeinbildung. The analysis is structured after Heinrich Winter’s basic experiences regarding mathematical Allgemeinbildung. The review reveals both challenges and potentials. In particular, the handling of data, the role of outsourcing, and the lack of empirical research are discussed regarding the aim of Allgemeinbildung in the Danish school.